Patient perspectives on systematic client feedback in Dutch outpatient mental healthcare, a qualitative case reports study - Bram Bovendeerd; Kim de Jong; Erik de Groot; Jos de Keijser (BMC, 2024)
Abstract Objective The added value of systematic client feedback (SCF) to psychotherapy can be affected by patient perspectives, both in a positive and negative way, and is influenced by cultural factors as well. Current study explores patients' perspectives on use and optimization of SCF in Dutch outpatient mental healthcare. Primary aim of present study is to generate implications for daily practice and optimize SCF implementation, particularly for the Netherlands. Method Four patients suffering from mild to moderate psychological disorders were in-depth interviewed on their perspective on the use of SCF, when the Partners for Change Outcome Management System (PCOMS, high frequent), the Outcome Questionnaire (OQ-45, low frequent) and the Mental Health Continuum Short Form (MHC-SF, low frequent) was added to treatment as usual in two Dutch outpatient mental healthcare centers offering brief psychological treatment. Interview topics were (a) SCF in general; (b) type of questionnaires; (c) frequency of use; (d) effect of SCF on therapy; and (e) perceived added value of SCF. A SCF expert team analyzed the data through reflexive Thematic Analysis. Results We identified three themes, all of which have two sub-themes: (a) Requirements to use SCF, with sub-themes (a1) Balance between effort to complete SCF and perceived validity, and (a2) Balance between used frequency and perceived validity; (b) Modifiers for test-taking attitude, with subthemes (b1) SCF as an embedded part of therapy, and (b2) Quality of Therapist-Client alignment; and (c) Effects on therapeutic process, with subthemes (c1) Focus on task and goals, and shared responsibility, and (c2) Effects on outcome and satisfaction. Conclusions Adding SCF to therapy can be perceived as helpful by patients in psychotherapy if two conditions are met: (1) Creating a right balance between effort and yield for SCF to be used at all; and (2) embedding SCF as an integral part of therapy, through therapist-client alignment. Throughout the progression of therapy, it might be useful to perceive SCF and therapy as communicating vessels; according to patients it is not only necessary to adjust therapy based on SCF, but also to adjust SCF based on the course of therapy. Trial Registration This trial was registered on September 30, 2015 in the Dutch Trial Register NTR5466. The Medical Ethics Committee of the University of Twente (Enschede) approved this study (registration number: K15-11, METC Twente).